FEATURES OF THE WORKPLACE OF PERSONS WORKING OUTSIDE THE EMPLOYER’S LOCATION: LEGAL ASPECTS - Vyshnovetska, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to determine the peculiarities of the workplace of persons working outside the employer’s location and modern approaches to the workplace as an element of work organization. The methodological basis of the study comprises documentary analysis and synthesis, comparative analysis, cognitive-analytical methods, as well as methods of systematization and generalization. Results: a concept of the workplace as a classic element of work organization in organizational, technical, ergonomic and legal aspects is clarified and differentiating features of the workplaces of persons working outside the employer’s location are determined. Discussion: a differentiating feature of home work is that there is an attachment to the worker’s place of residence, which is the actual workplace for him/her. For remote workers, the workplace is neither factually nor legally significant. A key differentiating feature of remote work from the traditional work format is that the workplace itself does not matter at all, instead, the use of information and communication technologies and the technical possibility of communication with the employer are important. Analizing the judicial practice, it was concluded that a fixed workplace is a workplace that is located directly at the enterprise. Instead, the workplace, which does not have a clear fixation in the spatial dimension, is called as mobile. Such is the workplace of the employees with a traveling and mobile nature of work, which is characterized by a constant change of work zones in which the labour function is performed, the employees who perform work on the road and the employees who drive vehicles, whose workplace is located in the transport area itself means. If the employee’s workplace is located outside the location of the employer, such workplace is remote. We share a position of those scientists who believe that a category “remote work” is a collective concept that covers both remote and home work. Remote work is a generic feature, which means its performance at a distance from the location of the employer and which is characteristic of such types as remote and home work. Thus, the remote workplaces (i.e., those located far from the location of the employer) includes first of all the workplaces of the remote workers and the workplaces of the home workers. What they have in common is that these types of work are performed outside the employer’s premises. The great thing is that the homemaker’s workplace always has a clear fixation in the spatial dimension, as it is always located in a specific living space. The remote worker’s workplace is mobile.